Benthic Foraminifera and Productivity Regimes in the Kveithola Trough (Barents Sea)—Ecological Implications in a Changing Arctic and Actuopaleontological Meaning - Anna Sabbatini; Matteo Bazzaro; Francesca Caridi; Cinzia De Vittor; Valentina Esposito; Renata Giulia Lucchi; Alessandra Negri; Caterina Morigi (Journal of Marine Science and Engineering, 2023)
The rapid response of benthic foraminifera to organic carbon flux to the seafloor makes them promising bioindicators for evaluating the organic carbon stored in marine sediments. Fjords have been described as hotspots for carbon burial, potentially playing a key role within the carbon cycle as climate regulators over multiple timescales. Nevertheless, little is known about organic carbon-rich sediments in Arctic open shelves and their role in global carbon sequestration. To this aim, four sites have been sampled along a W-E transect across the Kveithola Trough located in the NW Barents Sea. Living (stained) benthic foraminiferal density, biodiversity and vertical distribution in the sediment were analysed together with the biogeochemical and sedimentological data. We identified two main depositional environments based on the relationship between benthic foraminiferal assemblages and carbon content in the sediments: (1) an oligotrophic land-derived organic matter region located in the outer part of the trough influenced by the warm and saline Atlantic Water; and (2) a stressed eutrophic environment, with high-content of metabolizable organic matter in the inner part of the trough, which comprises the main drift and the Northern flank of the trough. The freshness and good nutritional quality of the organic matter detected in the inner region could be the result of the better preservation of the organic matter itself, basically driven by the rapid burial of fine-grained organic-rich sediments enhanced by the cold and less saline Arctic Water coming from the Barents Sea. We conclude that foraminifera provide a tool to describe the Kveithola depositional environment as a carbon burial hotspot in a changing Arctic area subjected to a pulse of fresh food intended as biopolymeric carbon.